Infrared imaging as a non-destructive testing method for geopolymer concrete - Kusbiantoro, A.; A. H., Ismail; S. K., Jema'in; Khairunisa, Muthusamy; F. F., Zainal (Polish Academy of Sciences, 2023)
Non-destructive testing (NDT) is generally used to estimate the compressive strength of concrete material without compromising its structural integrity. However, the available testing methods on the market have particular limitations that may restrict the accuracy of the results. Therefore, this study aimed to develop a new technique for measuring the compressive strength of geopolymer concrete using infrared imaging analysis and Thermal Diameter Variation (TDV) rate. The compressive strength range was designed within the target strength of 20, 30 and 40 MPa. The infrared image was captured on the preheated concrete surface using FLIR-ONE infrared camera. Based on the correlation between TDV rate and compressive strength, higher accuracy was obtained in the orange contour with an R of 0.925 than in the red contour with an R2 of 0.8867. It is apparent that infrared imaging analysis has excellent reliability to be used as an alternative NDT by focusing on the warmer region during the procedure